2016
DOI: 10.1111/tpj.13315
|View full text |Cite
|
Sign up to set email alerts
|

Tricin‐lignins: occurrence and quantitation of tricin in relation to phylogeny

Abstract: SUMMARYTricin [5,7-dihydroxy-2-(4-hydroxy-3,5-dimethoxyphenyl)-4H-chromen-4-one], a flavone, was recently established as an authentic monomer in grass lignification that likely functions as a nucleation site. It is linked onto lignin as an aryl alkyl ether by radical coupling with monolignols or their acylated analogs. However, the level of tricin that incorporates into lignin remains unclear. Herein, three lignin characterization methods: acidolysis; thioacidolysis; and derivatization followed by reductive cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 58 publications
3
141
1
Order By: Relevance
“…Therefore, the increased frequencies of b-b units C and C9, along with the reduced signals from b-O-4 units A, are signs of increased monolignol dimerization in the absence of tricin. This finding is in agreement with the fact that the level of b-b units had an opposite trend to the level of tricin units in a series of wheat straw lignin fractions that differed in M r (Lan et al, 2016b). On the other hand, we cannot exclude the possibility that the shifts in coupling frequencies are a consequence of the increased flux toward monolignols or acylated monolignols in C2-Idf mutants, as determined by the increased Klason lignin content in these plants, rather than the absence of tricin per se.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, the increased frequencies of b-b units C and C9, along with the reduced signals from b-O-4 units A, are signs of increased monolignol dimerization in the absence of tricin. This finding is in agreement with the fact that the level of b-b units had an opposite trend to the level of tricin units in a series of wheat straw lignin fractions that differed in M r (Lan et al, 2016b). On the other hand, we cannot exclude the possibility that the shifts in coupling frequencies are a consequence of the increased flux toward monolignols or acylated monolignols in C2-Idf mutants, as determined by the increased Klason lignin content in these plants, rather than the absence of tricin per se.…”
Section: Discussionsupporting
confidence: 90%
“…*, 0.05 . P $ 0.01; and ***, P , 0.001. overestimated in HSQC spectra, so analytical thioacidolysis was used to provide accurate quantitation of the level of incorporation (Lan et al, 2016b). Also upon accurate quantitation, the tricin content was higher in leaves (about 18 mg g 21 ) than in stems (about 7 mg g 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, extensive surveys have revealed that tricin-bound lignins exist abundantly, particularly in the monocot family Poaceae, which comprises grasses including cereals. They also have been found in some commelinid monocot families outside Poaceae, such as Arecaceae (palms) and Bromeliaceae (pineapples and relatives), the noncommelinid family Orchidaceae (the orchids), particularly in the genus Vanilla, and also in certain dicots (Rencoret et al, 2013;Wen et al, 2013;Del Río et al, 2015;Lan et al, 2015Lan et al, , 2016aLan et al, , 2016bKoshiba et al, 2017).…”
mentioning
confidence: 96%